Pendampingan Pemasaran Dan Branding Produk UMKM Simping Di Desa Mekargalih Kec. Jatiluhur Purwakarta - Fitrianingsih, Feti; Syauri, M Sofian; Jalaludin, Jalaludin (STIE Syariah Indonesia Purwakarta, 2022)
The number of MSMEs in the village of Mekargalih, Kec. Jatiluhur Purwakarta is quite a lot, such as scallop SMEs, various chips SMEs, pot craft SMEs, and others. Of the many MSMEs, there are several MSME actors who still market their products in the traditional way and still use simple labels/brands, making it difficult to attract consumers' buying interest. The reason they haven't marketed their products online is due to the lack of understanding of MSME actors on the importance of online marketing and product branding, as well as their limited ability in the world of technology (IPTEK). The aim of this PKM is to maximize the Marketing and Branding of MSME Simping Products in Mekargalih Village, Kec. Jatiluhur Purwakarta from the traditional system assisted by a digital system, as well as rebranding product appearance from a simple display to an attractive display or label in order to increase consumer appeal. The method used by this PKM uses the method of providing material, rebranding labels, and mentoring. The conclusion of community service activities with the title marketing assistance and branding of MSME scallop products in Mekargalih Village, Kec. Jatiluhur Purwakarta, the increase in sales of MSME scallop products, which were only a few packs a day, now has reached 50-200 packs a day. In addition to marketing and branding assistance programs for MSME scallop products, the PKM team also has other supporting programs, namely recitation at the Al-Mustaba Mosque, Private English and Calistung, and teaching at RA Al-Irfan. These programs involve children around the village of Mekargalih, their response is very enthusiastic and they feel helped by this support program, besides being able to play they can also learn to improve their writing, reading and speaking English skills.